2012
DOI: 10.1002/esp.3347
|View full text |Cite
|
Sign up to set email alerts
|

Threshold of erosion of submarine bedrock landscapes by tidal currents

Abstract: Since sea level stabilized 7000 yr BP, shelf seas experiencing semi-diurnal tides will have been affected by streaming four times per day. If tidal erosion of bedrock were even only marginally efficient, the~10 million streamings since then should have left geomorphological imprints. We examine high-resolution multibeam sonar data from three areas with extreme tidal currents. The Minas Passage (Bay of Fundy) experiencing 8-knot surface tidal currents was surveyed in 2007 with a multibeam sonar. In an area near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Northern Palaeovalley due to tidal scour, as this was shown to have minor erosive potential in neighbouring 451 areas (Mitchell et al, 2013). The study area also shows preservation of subtle features such as the 452 secondary drainages which again points to tidal scour being ineffective at eroding bedrock.…”
Section: A and F 295mentioning
confidence: 83%
“…Northern Palaeovalley due to tidal scour, as this was shown to have minor erosive potential in neighbouring 451 areas (Mitchell et al, 2013). The study area also shows preservation of subtle features such as the 452 secondary drainages which again points to tidal scour being ineffective at eroding bedrock.…”
Section: A and F 295mentioning
confidence: 83%
“…Rapid sand transport across the Helwick Bank crest, in the form of reattaching dune crests, has been observed (Schmitt and Mitchell, 2014), which indicates storm waves could have resulted in our observations of a 'flattening sand bank crest'. Furthermore, work by Mitchell et al (2012) indicates sand dune trains overlying bedrock have been observed at the nearshore termination of Helwick Bank, which may be the outcome of an erosion phase. Therefore, it appears that storm wave events were responsible for the observed interannual changes to Helwick Bank.…”
Section: Discussionmentioning
confidence: 95%
“…A further two time-varying water-level scenarios of a flooding (MLWS to MHWS) and ebbing spring tide (MHWS to MLWS) were also simulated; see Table 3. Observations at Helwick Bank indicate highly mobile sand dunes with a grain size of 400 lm (Mitchell et al, 2012;Schmitt and Mitchell, 2014;Schmitt, Mitchell, and Ramsey, 2008), which, during times of extreme storm waves, could become washed out (i.e. flat bed).…”
Section: Simulations Of Storm Impacts On Helwick Bankmentioning
confidence: 98%
See 1 more Smart Citation
“…However, most geological processes are unlikely to reverse within a few ky; we know of no examples of normal fault movements reversing over such timescales in extensional environments such as that considered here. Furthermore, currents measured over Hanish Sill are ∼1 ms −1 (Pratt et al, 1999), which is too small to cause erosion of bedrock (Mitchell et al, 2012), so any emplaced volcanic materials are unlikely to been fully removed by currents. We therefore prefer to consider the short-period deviations from the other sealevel models in Fig.…”
Section: Introductionmentioning
confidence: 99%